Bilateral greater Occipital Nerve Block for Headache after corrective Spinal Surgery: A Case Report - Edmundo Pereira de Souza Neto; José Luis Martinez; Kathryn Dekoven; Francoise Yung; Sandra Lesage (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Post-Dural Puncture Headache is a common complication for patients with dural puncture and if untreated, it can result in complications such as subdural hematoma and seizures. The aim of this case report is to present a case of headache after corrective spinal surgery for idiopathic scoliosis resolved with a BGON block.